2013
DOI: 10.12816/0001545
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Device Size for Atrial Septal Defect Closure Using Transesophageal Echocardiography Without Balloon-Sizing : Experience at Queen Alia Heart Institute

Abstract: Objective: To report our experience of percutaneous atrial septal defect closure using different devices, stressing the role of transesophageal echocardiography in defect sizing between December 2010 and December 2012. Methods: Retrospective study of 105 patients that had hemodynamically significant left to right shunt (≥1.5:1), atrial septal defect secundum underwent trans-catheter closure of the septal defect using different devices at Queen Alia Heart Institute between December 2010 and December 2012. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…Rania et al demonstrated the mean upsizing of the device was around 2.5mm ± 3.5mm. 18 The majority of the upsizing were between 2-4 mm, the mean of 3mm ± SD 3.5, which correlate better with the study of Amin and Dauffers. 19 However, none of study demonstrated the mathematical relation of sizing of device which may have significant role in ASD closure.…”
Section: Discussionsupporting
confidence: 62%
“…Rania et al demonstrated the mean upsizing of the device was around 2.5mm ± 3.5mm. 18 The majority of the upsizing were between 2-4 mm, the mean of 3mm ± SD 3.5, which correlate better with the study of Amin and Dauffers. 19 However, none of study demonstrated the mathematical relation of sizing of device which may have significant role in ASD closure.…”
Section: Discussionsupporting
confidence: 62%